Current Situation, Problems, and Needs in the Management of Educational Technology and Communication in Vocational Institutions in Thailand - Songsri, Sutisa; Chumraksa, Chatchawan; Sirikunpipat, Pattana; Kasinant, Chintana (Journal of Technical and Engineering Education, 2025)
This research aimed to study the current situation, problems, and needs regarding the management of technology and educational communication in vocational institutions in Thailand. The sample group consisted of 17,151 including school administrators, teachers, and students under the Office of Vocational Education Commission. The research instrument was a questionnaire. The findings revealed that 1) administrators, teachers, and students identified the most commonly practiced aspect as the learning environment, while the least practiced aspect was professional knowledge and skills. 2) The administrators and teachers perceived the most significant problem as research, while the learning environment was the least problematic aspect. Conversely, students identified research as the most problematic aspect and professional knowledge and skills as the least problematic. 3) Regarding needs administrators indicated the highest need for development in knowledge, with the lowest need for professional knowledge and skills. Teachers expressed the highest need for development in knowledge and the lowest in research. Students indicated the highest need for development in knowledge and the learning environment, while research was perceived as the least needed area for development.